The Early Dental Visit: Timing, Rationale, and Road Blocks: Timing and Barriers to Early Dental Visits - Shahid, Amira; Muneer, Maliha; Munawar, Mehwish; Khurram, Maleeha; Iqbal, Sarosh; Khan, Nida (Pakistan Journal of Health Sciences, 2025)
A child's first dental visit at the first tooth eruption or at one year of age has the potential to prevent early disease treatment and modify the child's dental behavior. Objectives: To assess the knowledge of parents about age, reasons, and hurdles to first dental visits of children. Methods: This cross-sectional questionnaire-based study was carried out at the outpatient department at Madina Teaching Hospital, Faisalabad, in a period of six months from February 2023 to July 2023. The parents of children<1 to 15 years meeting the inclusion criteria and who gave verbal consent were included in the study. Results: A total of 180 children (104 male, 76 female) enrolled in the study. Only 8.9 % (n=16) of parents were aware of the recommended time for the first dental visit of children. Most parents (46.7%, n=84) believed that children should visit a dentist at the time of a dental problem. Common reasons for the first dental visit were dental caries (50.6%, n=91) and dental pain (22.2%, n=40). Parents reported having time constraints (16.7%, n=30), believing primary teeth unimportant (13.3%, n=24) child cooperation problems (13.3%, n=24) as hurdles to early dental visits. Conclusions: Most participants were unaware of recommendations, and some had misbeliefs that led to a delay in the first dental visit of children. Efforts should be made to educate the local population about the proposed time and importance of the first dental visit of children.